2022
DOI: 10.1002/1878-0261.13351
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of CDK4 phosphorylation predicts high sensitivity of pleural mesotheliomas to CDK4/6 inhibition

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 175 publications
3
11
0
Order By: Relevance
“…By contrast, the homologous T177 phosphorylation on CDK6 is not regulated and is generally absent or weak ( 13 , 25 ). In our previous studies in breast tumors ( 26 ) and pleural mesotheliomas ( 27 ), we observed a variable presence of CDK4 T172-phosphorylation in most tumors. Its absence however, was also observed in some highly proliferative tumors, in association with the main mechanisms of resistance to CDK4/6i, including RB defects or inactivation, and high expressions of CDKN2A (p16), CCNE1 (cyclin E1) and E2F1 ( 26 29 ).…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…By contrast, the homologous T177 phosphorylation on CDK6 is not regulated and is generally absent or weak ( 13 , 25 ). In our previous studies in breast tumors ( 26 ) and pleural mesotheliomas ( 27 ), we observed a variable presence of CDK4 T172-phosphorylation in most tumors. Its absence however, was also observed in some highly proliferative tumors, in association with the main mechanisms of resistance to CDK4/6i, including RB defects or inactivation, and high expressions of CDKN2A (p16), CCNE1 (cyclin E1) and E2F1 ( 26 29 ).…”
Section: Introductionmentioning
confidence: 66%
“…This latter form does not incorporate [32P] phosphate and binds to p16 but only weakly to cyclins D ( 13 ). The abundance ratio of the T172-phosphorylated form (spot 3) over the form separated in spot 2 allowed us to define three types of profiles (L for low, H for high and A for absent phosphorylated CDK4), as previously reported ( 26 , 27 ). All WDTC exhibited the T172-phosphorylated form of CDK4 (n=29).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations